Acehnese Swear Word in Dewantara Sub-District Nort Aceh - Harliyana, Iba; Safriandi, Safriandi; Yani, Putri Riski; Fitria, Afnita (SAINTIS Publishing, 2024)
This study examines the Acehnese language curses in Dewantara District, North Aceh. The purpose of this study is to describe the form of curses in Acehnese language in Dewantara District, North Aceh. This study is a qualitative descriptive study. The location of this research was carried out in 4 villages in Dewantara District, North Aceh, namely Bluka Teubai Village, Bangka Jaya, Geulumpang Sulu Timu, and Geulumpang Sulu Barat. The data source for this study was native Acehnese speakers in Dewantara District. The data collection technique for this study used the listening and speaking techniques. Based on the results of the study, it was found that there were 47 curses in Acehnese language in Dewantara District, North Aceh Regency. After analyzing the research data, it was found that the form of curses consisted of 9 curses in the form of words, 17 curses in the form of phrases, 14 curses in the form of clauses and 7 curses in the form of compound words. Based on the results of the data analysis, the dominant use of curses by the community in Dewantara District, North Aceh, is more dominant in the form of curses in clauses.